(untitled) (The Geographic Base, 2019)
Climate change is now a global issue and its impact on different sectors like water sources, biodiversity, health, livestock, and livelihood are already seen. Climate change is accelerating due to the emission of greenhouse gases produced by anthropogenic activities. Though Nepal’s contribution to greenhouse gases is negligible compared to developed countries, its risk to climate change is very high. Thus, it extremely important to understand the current scenario of climate change of Nepal. Hence, this article reviews and compares the published articles which studies the pattern and trend of climate change of the time period of at least 30 years. Most of the article shows increasing trend of temperature. According to the recent study, maximum temperature was found to be increasing by 0.05°C/year and minimum temperature was found to increase by 0.03°C/year. Though, the trend of precipitation in Nepal is not clear like temperature most of the studies have concluded increasing in monsoon precipitation in coming years.